CRITICAL LIMB ISCHEMIA IN 27 YEARS OLD HIV PATIENT: A CASE REPORT - Ade Yonata; Hayatun Nufus; Teguh Harjono Karjadi (Fakultas Kedokteran Universitas Lampung, 2014)
The prevalence of peripheral arterial disease (PAD) is high in the HIV-infected population and is much higher than expected in the general population. A 27 years old male patient came to Cipto Mangunkusumo General Hospital (RSCM) with chief complaint of pain on right leg which worsened since 2 days prior admission. Patient was diagnosed HIV positive 8 months prior admission and had already on ARV treatment Duviral (AZT/3TC) and Alluvia (lopinavir/ritonavir) since then. CT angiography showed stenosis of femoral communis artery with total stenosis of right posterior tibialis artery. Patient was diagnosed with criticl limb ischemia and got amputation. Some theories of PAD mechanism in HIV patient have been proposed. Highly ac tive antiretroviral therapy (HAART) has decreased the mortality and illnesses related to HIV infection. However, a variety of atherogenic metabolic abnormalities, including dyslipidemia, lipodystrophy, and also thickened intima-media thickness have been observed after the introduction of HAART, especially using Protease Inhibitors. Human Imunodeficiency Virus itself is also thought to have role in injury to the arterial wall such as via chemokine CCL2/MCP-1, a critical mediator of atherosclerosis. All HIV-infected patients candidate to antiretroviral therapy and patients already under treatment should undergo an assessment that includes the evaluation of the cardiovascular risk. [JuKe Unila 2014; 4(8):218-224]